A Prospective Study of Postoperative Lymphedema After Surgery for Cervical Cancer. Issue 5 (1st June 2010) - Halaska, Michael J.; Novackova, Marta; Mala, Ivana; Pluta, Marek; Chmel, Roman; Stankusova, Hana; Robova, Helena; Rob, Lukas
Abstract : Objective: Lymphedema is a severe postoperative complication in oncological surgery. Multifrequency bioelectrical impedance analysis (MFBIA) is a new method for early lymphedema detection. The objective was to establish the methodology of MFBIA for lower-limb lymphedema and to detect a lymphedema in patients undergoing cervical cancer surgery. Methods: From a population of 60 patients undergoing cervical cancer surgery, 39 underwent radical hysterectomy Wertheim III (RAD group), and 21 underwent conservative surgery (laparoscopic lymphadenectomy plus simple trachelectomy/simple hysterectomy - CONS group). A control group of 29 patients (CONTR group) was used to determine the SD of impedance at zero frequency ( R 0 ). Patients were examined before surgery and at 3 and 6 months after surgery by MFBIA and by measuring the circumference of the lower limbs. Results: No differences were found between the CONS and RAD groups on age, height, weight, and histopathologic type of tumor. However, the number of dissected lymph nodes differed significantly between the groups (17.3 in the CONS group vs 25.8 in the RAD group, P = 0.0012). The SD of R 0 in the CONTR group was 36.0 and 39.0 for the right and the left leg, respectively. No difference in prevalence of lymphedema based on circumference method was found (35.9% in the RAD and 47.6% in the CONS groups, not statistically significant). Conclusions: No difference in the prevalence of lymphedema was found between the CONS and RAD groups. A methodology for MFBIA for the detection of lower-limb lymphedema was described.